Inclusão disciplinada: um estudo sobre os institutos federais - Martins, Gilmar Vieira (2022)
This research has as its theme educational and social inclusion in the Federal Institutes of Education, Science and Technology. Our research locus was the Federal Institutes. The main categories of work and research were inclusion, governmentality and professional and technological education. The main objective was to understand, within the scope of educational inclusion policies, how the Political-Institutional and Political-Pedagogical elements dialogue with the influences of neoliberal capitalism. From an epistemological point of view, we took poststructuralist theories as references insofar as they allowed us to show the policy in its dialogic interaction of governmentality with the compositional foundations of the construction of the inclusion policy. We work with authors such as Foucault, Veiga-Neto, Kuenzer, Martins, Pacheco among others. Methodologically, we chose to adopt a qualitative and quantitative approach, of an exploratory type, and as a data collection tool, we used a hybrid questionnaire survey, consisting of closed and open questions. From an analytical point of view, we used descriptive statistical analysis and discourse analysis as data analysis techniques. The thesis presented, which was partially confirmed, directed towards the understanding that the inclusion policies produced in the IFs, can, to a certain extent, be in line with the neoliberal needs of the dominant power, through the fabrication of subjectivities, essentially and through the policies inclusive environments surrounding the social and educational context, however, we presuppose that they are the result of responses that come from the signs present in the documents of multilateral organizations and from supposed new requirements related to the contemporary scenario. According to our conjectures, we carefully conclude that the inclusion process, both educational and social, present in the documents that consolidate the Political-Institutional and Political-Pedagogical foundations of the Federal Institutes, as well as, in the empirical discourses, leads us to the perceptual nuances of existence, perhaps, of neoliberal influences.